Low thermal conductivity carbon fibrous composite nanomaterial enabled by multi-scale porous structure. (15th November 2017) - Gbewonyo, Spero; Carpenter, Alexis W.; Gause, Charles B.; Mucha, Nikhil Reddy; Zhang, Lifeng
Abstract: Low thermal conductivity carbon is a type of material for special uses such as thermal insulation/protection and particularly for ablative thermal protection material of reentry vehicles and rocket engine components. In this research, a low thermal conductivity carbon nanofibrous material was prepared by electrospinning polyacrylonitrile (PAN) with poly (methyl methacrylate) (PMMA) as well as silica nanoparticles (SNPs) followed by stabilization and carbonization. Morphology and structure of this carbon nanofibrous material were characterized by electron microscope, X-ray diffraction, Raman spectroscopy, and BET surface area analysis and correlated with its thermal conductivity. Introduction of PMMA and SNPs to PAN precursor nanofibers through multi-component electrospinning enabled a unique concurrent multi-scale (micro-, submicro- and nano-) porous structure in the resultant carbon nanofibrous mat and synergistically reduced the thermal conductivity by up to 98% with respect to the non-porous carbon film counterpart. This research demonstrated a novel and effective way to design and manufacture low thermal conductivity carbon materials. Graphical abstract: Highlights: A low thermal conductivity carbon fibrous material was prepared through electrospinning Concurrent micro-, submicro-, and nano-porous carbon structure was created Synergistic contribution of multi-scale porous structure to final low thermal conductivity carbon was revealed Electrospun carbon nanofibrous mat showed up to 98% thermal conductivity reduction compared to carbon film counterpart